Pengembangan Produk Minuman Marqualoe (Markisa Lidah Buaya) Instan (Studi Kasus di KWT Mekar Sari Temanggung) - Rizky Dyah Anggraeni; Nur Rohmah Lufti Ayuni; Siti Astuti (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2025)
The Marqualoe product (passion fruit aloe vera) is a ready-to-drink product produced by KWT Mekar Sari. It has a disadvantage of relatively short shelf life, innovation was carried out to developed the product into instant Marqualoe with extended shelf life. The research aims to determine the best formulation of instant Marqualoe products based on organoleptic testing, identify the most preferred packaging attribute combination of instant Marqualoe products based on conjoint analysis., and determine the selling price of the instant Marqualoe product. This research was conducted at KWT Mekar Sari carried out from December 2023 to May 2024. The research used organoleptic test methods, conjoint analysis, and cost-plus pricing with a full costing approach. The obtained data was processed using Microsoft Excel and SPSS 26 analysis tools. The results showed that selected instant Marqualoe formulation was formulation 1 (500 g of aloe vera, 1000 g of sugar, 250 ml of passion fruit juice with a preference percentage of 87%. The combination of product packaging attributes that consumers like most is standing pouch flat bottom packaging, aluminum foil material, packaging label 2, and a net weight of 125 grams. The selling price of this product is set at IDR 9.884,82.